Pengaruh Ukuran Perusahaan dan Leverage Terhadap Profitabilitas dan Nilai Perusahaan - Setiadewi, Kadek Ayu Yogamurti; Purbawangsa, Ida Bagus Anom (E-Jurnal Manajemen, 2015)
Improving corporate profits and maximize the value of the company is interrelated objectives to improve the welfare of shareholders, so it is an important consideration in maintaining the continuity of the company. Location of the research done on food and beverage companies in the Stock Exchange of 10 sample companies. The data collection was done by using nonparticipant observation through financial statements. The results of analysis with proven track profitability analysis technique which acts as the main intervening variable is not able to mediate firm size and leverage on firm value. The results showed that the size of the company and the leverage effect, but not statistically significant on profitability, whereas no significant effect of firm size on leverage. Company size in this study was not statistically significant effect on firm value, while leverage and profitability have a significant positive effect on firm value.
Keywords: firm size, leverage, profitability and corporate value